Evaluation of the Family Liaison Officer role during the COVID-19 pandemic - Luke Hughes; Lisa Anderton; Rachel Taylor (Qualitative Research in Medicine & Healthcare)
Communication within healthcare settings is often a subject of contention for patients’ families at the best of times; however, contention was greatly magnified in the United Kingdom by restrictions on hospital visitations during the early stage of the COVID-19 pandemic. To support communication between families and patients, a central London hospital introduced the role of the family liaison officer (FLO). This study was designed to evaluate the rapid implementation of the FLO and to explore potential for it to become a standard role. Semi-structured interviews were conducted with five FLOs and seven colleagues who had worked alongside them between April and June, 2020. Two versions of the role emerged based on FLOs’ previous background: clinical (primarily nurses) and pastoral (primarily play specialists). The FLO became a key role during the pandemic in facilitating communication between patients, clinical teams, and families. Challenges associated with the role reflect the speed in which it was implemented. It was evident to those in the role, and clinicians who the role was supporting, that it had potential to help improve hospital communication and the work of healthcare staff beyond the pandemic.